Sintetični molekulski motorji - Černigoj, Jernej (Matrika, 2016)
In this article I present some basic characteristics of synthetic molecular motors and their thermodynamic working principles. In detail I describe the functioning of synthetic protein motors and molecular spiders. I also show a few examples of studies relating their properties to efficiency and performance.
Keywords: molecular motors; molecular spiders; molekularni pajki; molekulski motorji; sintetični proteinski motorji; synthetic protein motors